(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: This study examines the role of training programmes, handloom expos, and tourism in empowering women artisans in Assam. Using secondary data from 2011 to 2023, correlation and trend analyses are employed to evaluate the impact of policy, employment outcomes, and market access. Results show little correlation between training and stable employment, but a strong positive relationship (r=0.99) between exposure and sales revenue, emphasising their economic significance. Tourism demonstrated limited influence on handloom demand. The findings underscore the need for integrated strategies that combine skill development, market access, and tourism to support sustainable livelihoods for women weavers and preserve indigenous textile traditions.